2021
DOI: 10.1371/journal.pone.0253255
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of Musa balbisiana populations in Vietnam and its implications for the conservation of banana crop wild relatives

Abstract: Crop wild relatives (CWR) are an indispensable source of alleles to improve desired traits in related crops. While knowledge on the genetic diversity of CWR can facilitate breeding and conservation strategies, it has poorly been assessed. Cultivated bananas are a major part of the diet and income of hundreds of millions of people and can be considered as one of the most important fruits worldwide. Here, we assessed the genetic diversity and structure of Musa balbisiana, an important CWR of plantains, dessert a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 86 publications
2
15
0
1
Order By: Relevance
“…The genetic diversity of bananas has been carried out using different molecular markers, and significant success has been made for analyzing commercial cultivars and some wild germplasm 34 , 35 . However, not much is known about the local germplasm, which harbors important traits for adaptation to local climatic conditions and small-holdings.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic diversity of bananas has been carried out using different molecular markers, and significant success has been made for analyzing commercial cultivars and some wild germplasm 34 , 35 . However, not much is known about the local germplasm, which harbors important traits for adaptation to local climatic conditions and small-holdings.…”
Section: Resultsmentioning
confidence: 99%
“…From all assessed microsatellite loci, BB_CT-33, BB_GAA-4, BB_CT-6, and BB_CT-8 were the most informative. While five loci were uninformative (monomorphic) for the samples included in this study (Mbg02, Mbg04, BB_AAC-3, BB_CT-7, and Mbg01), they were retained for all analyses in order to be able to compare results with the studies of Bawin et al ( 2019 ) and Mertens et al ( 2021a ). The proportion of polymorphic loci ( %P ) and average number of different alleles ( Na ) ranged from 0 to 66.67 and 1.000 to 2.167 respectively (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study of Mertens et al ( 2021a ) demonstrated that Chinese and northern Vietnamese populations contained high genetic diversity which is important to conserve while additional sampling in Central Vietnam was recommended based on the high genetic diversity and number of unique alleles in the two sampled populations. Vietnamese populations could be distinguished from Chinese populations, with even further substructuring of Vietnamese populations at higher K -values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations